Observation of Weak Counterion Size Dependence of Thermoelectric Transport in Ion Exchange Doped Conducting Polymers Across a Wide Range of Conductivities. Issue 9 (10th January 2023) - Chen, Chen; Jacobs, Ian E.; Kang, Keehoon; Lin, Yue; Jellett, Cameron; Kang, Boseok; Lee, Seon Baek; Huang, Yuxuan; BaloochQarai, Mohammad; Ghosh, Raja; Statz, Martin; Wood, William; et al.
Abstract: Conducting polymers are of interest for a broad range of applications from bioelectronics to thermoelectrics. The factors that govern their complex charge transport physics include the structural disorder present in these highly doped polymer films and the Coulombic interactions between the electronic charge carriers and the dopant counterions. Previous studies have shown that at low doping levels carriers are strongly trapped in the vicinity of the counterions, while at high doping levels charge transport is not limited by Coulombic trapping, which manifests itself in the conductivity being independent of the size of the dopant counterion. Here a recently developed ion exchange doping method is used to investigate the ion size dependence of a semicrystalline polythiophene‐based model system across a wide range of conductivities. It is found that the regime in which the charge and thermoelectric transport is not or only weakly dependent on ion size, extends to surprisingly low conductivities. This surprising observation is explained by a heterogeneous doping that involves doping of the amorphous domains to high doping levels first before doping of the ordered, crystalline domains occurs. The study provides new insights into how the thermoelectric physics of conducting polymers evolves as a function of doping level. Abstract : In ion exchange doped polythiophene polymers the conductivity is independent of the size of the dopant counterion at the highest doping concentrations/conductivities (>100 S cm −1 ). At intermediate conductivities (10 −1 to 10 2 S cm −1 ) doping occurs primarily in the amorphous domains, leading to an unexpected carrier delocalization due to high local carrier concentrations and a similar absence of counterion‐induced Coulombic trapping.